The Economic Value of Breaking Bad: Misbehavior, Schooling and the Labor Market - Nicholas W. Papageorge; Victor Ronda; Yu Zheng (Institute of Labor Economics (IZA), 2017)
Prevailing research argues that childhood misbehavior in the classroom is bad for schooling and, presumably, bad for adult outcomes. In contrast, we argue that childhood misbehavior represents some underlying non-cognitive skills that are valuable in the labor market. We follow work from psychology and categorize observed classroom misbehavior into two underlying latent factors. We then estimate a model of educational attainment and earnings outcomes, allowing the impact of each of the two factors to vary by outcome. We find one of the factors, labeled in the psychological literature as externalizing behavior (and linked, for example, to aggression), reduces educational attainment yet increases earnings. Unlike most models where non-cognitive skills that increase human capital through education also increase labor market skills, our findings illustrate how some non-cognitive skills can be productive in some economic contexts and counter-productive in others. Policies designed to promote human capital accumulation could therefore have mixed effects or even negative economic consequences, especially for policies that target non-cognitive skill formation for children or adolescents which are aimed solely at improving educational outcomes.
Keywords: J10; J20; I20; 330; non-cognitive skills; education; labor